Fungsi Reinterpretasi pada Perkembangan Tari Orek-Orek di Kabupaten Ngawi - Septa Riya Eka Puspita Sari; Endang Murti; Harianto Harianto (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
This study aims to analyze the reinterpretation function in the development of Orek-Orek Dance in Ngawi Regency carried out by Sanggar Tari Sri Budaya. Orek-Orek Dance is a reinterpretation of the traditional folk art of Orek-Orek, which previously existed in the form of petilan performances or traveling folk theater that developed within the society of Ngawi Regency. This study employed a qualitative descriptive method with data collection techniques consisting of observation, interviews, and documentation. The research informants included the founder of Sanggar Tari Sri Budaya, representatives from the Department of Tourism and Culture of Ngawi Regency, and the local community of Ngawi Regency. The results of the study indicate that reinterpretation was carried out through the modernization of dance forms without eliminating traditional elements, choreography development, the use of digital media, and the creation of new functions for Orek-Orek Dance. Sanggar Tari Sri Budaya succeeded in establishing Orek-Orek Dance as a cultural identity of Ngawi Regency through youth training programs, cultural performances, and digital promotion. The reinterpretation process generated educational, social, creative economic, cultural identity, and modern performance functions. Furthermore, reinterpretation successfully maintained the existence of Orek-Orek Dance amidst the development of modern times so that it remains recognized by people across generations.